Book Review: Friedrich Engels and the Dialectics of Nature: Kaan Kangal - Cotrim, Felipe (2021)
Book Review: KANGAL, Kaan. Friedrich Engels and the Dialectics of Nature (Marx, Engels, and Marxisms). London: Palgrave Macmillan, 2020. xvi, 213 p.